Double exposure : resurveying the West with Timothy O'Sullivan, America's most mysterious war photographer - Sullivan, Robert, 1963- (Farrar, Straus and Giroux, 2024)
"A personal exploration of the history of the American West through the work of the nineteenth-century photographer Timothy O'Sullivan"--